Bearing Steel Structures for Installation of Railway Strain Gauge Scales - Klochko, L. I. (Science and Transport Progress, 2024)
Purpose. The main purpose of the publication is to compare the main technical and economic indicators of the two proposed structural variants of the support system for railway strain gauge scales for four-axle wide gauge railcars. This is due to the need to reconstruct and modernize the fixed assets of an industrial enterprise, in particular, to overhaul and replace old railway scales with modern electronic strain gauge scales. Also, the purpose of the work is related to the need to expand the range of railway cars for which the possibility of weighing is provided, including transport units of the foreign car fleet. Methodology. To achieve this goal, we analyzed the modern types of railroad cars for freight transportation, determined the main components of strain gauge scales for weighing the main types of cars, and developed a special support system to support the scale platform. The support system is provided in two design variants - with one spatial support frame and two separate flat support frames. Using the domestic design and computing complex SCAD, we built finite element models for both proposed design options. Based on the analysis of their stress-strain state, rational cross-sections were selected for each structural element, and the total mass was determined. Findings. A comparative analysis of the two developed structural solutions for the support system for modern railway strain gauges has revealed that the variant with two separate bearing frames has a lower weight by about 40 % compared to the variant with one spatial bearing frame. However, the manufacturability of its production is somewhat lower, since it involves 10 structural elements compared to 7 for variant No. 1. Originality. The numerical analysis made it possible to theoretically substantiate a more rational and efficient design solution for the support system for modern railway strain gauge scales. Practical value. A constructive variant of the steel support system has been developed and proposed for practical implementation, which is the most effective in terms of its technical and economic indicators for the existing conditions of an existing industrial enterprise. The developed design option was also coordinated with the project of major reconstruction of the building for weighing railroad cars.